Features of copper and manganese accumulation in the system «bottom – mollusks» of reservoirs of the city of Gomel and adjacent territories - Khadanovich, Albina; Makarenko, Tatyana; Pyrkh, Olga; Popicheva, Ekaterin (Journal of the Belarusian State University. Ecology, 2023)
Ecological assessment of copper and manganese accumulation by bottom sediments of aquatic ecosystems of Gomel and soft tissues of gastropod class mollusks (Gastropoda): common pond (Limneae stagnalis L.), river (Viviparus viviparus L.). An array of data was obtained for the period 2019–2021, based on which background concentrations of copper (8.57 mg/kg) and manganese (140.0 mg/kg) in bottom sediments were determined. The background content of copper in the tissues of the viviparts of the river and common pond was 8.33 mg/kg and 2.08 mg/kg; manganese -37.73 mg/kg and 49.34 mg/kg, respectively. In most of the studied reservoirs, the average copper content in bottom sediments in 2020 and 2021 decreased by 1.4–4.9 times compared to those in 2019, with the exception of the Dedno and Shapor lakes, in which the copper content increased. The range of variation of the metal compounds over the study period was 1.63–47.57 mg/kg. The high content of manganese is typical for bottom sediments of the Sozh River upstream of the city (Klenki village) and Volodkino Lake, and the concentration was found to be 2.0 times higher than the values typical for deposits of water bodies receiving contaminated surface runoff from Gomel. The decrease was noted for the bottom sediments of Shapor and U-shaped lakes, as well as sections of the Sozh river upstream and for the park area. The range of variation in the content of manganese compounds in bottom sediments was 31.28–917.57 mg/kg. The content of copper in viviparous tissues is higher in 2021 compared to 2019 and 2020. in all reservoirs, with the exception of the old river. Sozh, while the concentration of this metal changed in the range of 4.52–32.93 mg/kg. A decrease in the content of manganese in the soft tissues of viviparts was established from 2019 to 2021 in the river. Sozh above the city is 4.6 times, in the river. Sozh downstream – 4.8 times, in oz. Volodkino – 2.7 times, oz. Lyubenskoye – 2.1 times, the range was from 21.33 to 148.85 mg/kg. The copper content in the soft tissues of the pond was 0.85–7.19 mg/kg. The change in the content of manganese in the soft tissues of this mollusk species was non-monotonic in nature, and ranged from 28.73 to 118.58 mg/kg. The studied mollusk species should be classified as deconcentrators, since the calculated values of accumulation coefficients in most cases have values not exceeding one.